1988
DOI: 10.1007/bf01852270
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and inorganic phosphate secretion of rat ileum in vitro

Abstract: The unidirectional ileal transport of calcium (Ca) and inorganic phosphorus (Pi) of rats was measured in vitro with the modified Ussing technique. Animal preparation included 5/6 nephrectomy and EHDP treatment. They were compared to controls as well as to 1,25 (OH)2D3 supplemented rats. The results show that the ileum is a secretory organ for Ca and Pi, the serosa to mucosa transport (Jsm) exceeds the mucosa to serosa transport (Jms). Ca and Pi transport in sm direction is 1,25 (OH)2D3 independent but exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The importance of the ileum in intestinal phosphate uptake is unclear: while some studies have reported that the rat ileum has little or no capacity to absorb phosphate (Peters and Binswanger ; Marks et al. ), others have reported that the magnitude of phosphate absorption is similar in the duodenum, jejunum and ileum, perhaps in vivo attributable in part to differences in length (surface area for absorption) and transit time (resident time for absorption) (Cramer ; Kayne et al.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the ileum in intestinal phosphate uptake is unclear: while some studies have reported that the rat ileum has little or no capacity to absorb phosphate (Peters and Binswanger ; Marks et al. ), others have reported that the magnitude of phosphate absorption is similar in the duodenum, jejunum and ileum, perhaps in vivo attributable in part to differences in length (surface area for absorption) and transit time (resident time for absorption) (Cramer ; Kayne et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have revealed that the ileum of the rat has a very limited capacity to absorb phosphate. Indeed, it has been proposed that the rat ileum is a secretory site for calcium and phosphate, and that this occurs paracellularly (Peters & Binswanger, 1988). The factors controlling paracellular transport of phosphate are unknown, although ileal calcium secretion may be influenced by 1,25-dihydroxyvitamin D 3 (Peters & Binswanger, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been proposed that the rat ileum is a secretory site for calcium and phosphate, and that this occurs paracellularly (Peters & Binswanger, 1988). The factors controlling paracellular transport of phosphate are unknown, although ileal calcium secretion may be influenced by 1,25-dihydroxyvitamin D 3 (Peters & Binswanger, 1988). In contrast, the mouse small intestine has the ability to absorb phosphate in all segments examined, with the highest rate occurring in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…1 Rapid changes in transcellular distribution are effected primarily by systemic acid-base equilibrium and hormones such as insulin and catecholamines. 2 1,25(OH) 2 D stimulates intestinal PO4 absorption, 4 while parathyroid hormone (PTH) and osteocytederived fibroblast growth factor-23 (FGF-23) are the best-characterized phosphaturic factors.…”
mentioning
confidence: 99%